Health Resource Utilization of Labor Induction Versus Expectant Management. Issue 1 (24th March 2021) - Grobman, W.A.; Sandoval, G.; Reddy, U.M.; Tita, A.T.N.; Silver, R.M.; Mallett, G.; Hill, K.; Rice, M.M.; El-Sayed, Y.Y.; Wapner, R.J.; Rouse, D.J.; Saade, G.R.; et al.
Abstract : ( Am J Obstet Gynecol . 2020;222:369.e1–369.e11) The A Randomized Trial of Induction Versus Expectant Management (ARRIVE) trial was conducted to analyze the effects of planned elective induction of labor on 6000 low-risk nulliparous women in comparison with expectant management. The ARRIVE trial found that planned elective labor induction at 39 weeks resulted in decreased cesarean delivery, fewer pregnancies with hypertensive disorders, and decreased neonatal respiratory morbidity. The aim of the current study was to compare health care resource utilization between planned elective induction of labor at 39 weeks and expectant management in nulliparous women during 3 time periods: antepartum, delivery admission, and discharge until 8 weeks postpartum.